2015
DOI: 10.1002/jctb.4739
|View full text |Cite
|
Sign up to set email alerts
|

Manganese peroxidase and biomimetic systems applied toin vitrolignin degradation inEucalyptus grandismilled wood and kraft pulps

Abstract: BACKGROUND: Organoperoxyl radicals generated from unsaturated fatty acids can initiate lignin degradation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
(102 reference statements)
0
5
0
2
Order By: Relevance
“…The chelated Mn 3+ ions can also react with a certain co-oxidant (or mediator) to generate reactive radicals that can depolymerize the high redox potential non-phenolic lignin. Unsaturated fatty acids (UFA) and their lipid derivatives are such mediators that can be peroxidized to form highly reactive acyl and fatty acid peroxyl radicals acting on the non-phenolic lignin [ 7 11 ]. Other mediators such as glutathione (GSH) may also be involved in the formation of thiyl radicals, which are thought to be also involved in the degradation of recalcitrant compounds [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chelated Mn 3+ ions can also react with a certain co-oxidant (or mediator) to generate reactive radicals that can depolymerize the high redox potential non-phenolic lignin. Unsaturated fatty acids (UFA) and their lipid derivatives are such mediators that can be peroxidized to form highly reactive acyl and fatty acid peroxyl radicals acting on the non-phenolic lignin [ 7 11 ]. Other mediators such as glutathione (GSH) may also be involved in the formation of thiyl radicals, which are thought to be also involved in the degradation of recalcitrant compounds [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hattaka et al (2003) have reported several studies regarding the single ability of MnP to delignify lignocellulose, including writing that pure MnP from P. radiata has been reported to convert pine wood chips into small molecular weight fragments in the presence of Tween 80 and glucose-glucose oxidase complexes. Another study by Masarin, et al (2016) carried out the delignification process of Eucalyptus grandis wood chips using the partially purified MnP enzyme from C. subvermispora, showing that MnP was able to degrade lignin as much as 23.44%. The reaction conditions contained the equivalent of 200 IU MnP, Tween 60, MnSO4, and glucose -glucose oxidase complex at pH 4.5, temperature 27 C for 72 h, and agitated at 120 rpm [127].…”
Section: Application Of Ligninolytic Enzymesmentioning
confidence: 99%
“…Another study by Masarin, et al (2016) carried out the delignification process of Eucalyptus grandis wood chips using the partially purified MnP enzyme from C. subvermispora, showing that MnP was able to degrade lignin as much as 23.44%. The reaction conditions contained the equivalent of 200 IU MnP, Tween 60, MnSO4, and glucose -glucose oxidase complex at pH 4.5, temperature 27 C for 72 h, and agitated at 120 rpm [127].…”
Section: Application Of Ligninolytic Enzymesmentioning
confidence: 99%
“…Alguns dos tratamentos com O 2 em meio alcalino incluíram a presença Tween 80 para promover possíveis reações de peroxidação de lípidos e geração de radicais organoperoxila, capazes de decompor lignina (HORTA et al, 2011;JENSEN;HAMMEL, 1999;MASARIN et al, 2015).…”
Section: Tratamento Do Bagaço De Cana Com Sulfito Alcalino E Com O 2 unclassified
“…fungos podem degradar a lignina contida na parede celular sem causar a erosão da mesma, o que significa que deve haver sistemas degradativos que se baseiam na ação de compostos de baixa massa molar, visto que as enzimas produzidas por estes fungos não conseguem infiltrar a parede da celular lignificada(BLANCHETTE et al, 1997;CULLEN, 1998;MENDONÇA et al, 2004). Mn 2+ /H 2 O 2 como agente degradador de lignina in vitro, utilizando polpas kraft como substrato(MASARIN et al, 2015;MOREIRA et al, 2001). A maioria destes estudos visou a oxidação parcial ou a remoção de lignina de polpas kraft como uma etapa auxiliar no processo de branqueamento de polpas.…”
unclassified